Role of neighborhood social support in stress coping and psychological wellbeing during the COVID-19 pandemic: Evidence from Hubei, China. (May 2021) - Chen, Xi; Zou, Yuchun; Gao, Haiyan
Abstract: The COVID-19 pandemic that emerged in Wuhan, the capital city of Hubei province in China, has caused severe health problems and imposed a tremendous psychological impact on the public. This study investigated the risk and protective factors associated with psychological distress among Hubei residents during the peak of the outbreak. Data were obtained from a combined online and telephone survey of 1, 682 respondents. Various COVID-19-related stressors, including risk exposure, limited medical treatment access, inadequate basic supplies, reduced income, excessive exposure to COVID-19-related information, and perceived discrimination, were associated with psychological distress. Neighborhood social support can reduce psychological distress and buffer the effect of COVID-19-related stressors, whereas support from friends/relatives affected stress coping limitedly. Interventions to reduce stressors and promote neighborhood support are vital to reduce psychological distress during infectious disease outbreaks. Highlights: Risk exposure to COVID-19 had a positive effect on psychological distress. Income loss and inadequate supplies had positive effects on psychological distress. Perceived discrimination and exposure to COVID information can lead to distress. Neighborhood social support can reduce distress and buffer the effect of stressors. Support from friends or relatives had no main or buffering effects on distress.